Prevalence and Factors Associated with Insomnia in Elderly over 60 Years of Age at Family Medicine Outpatient Department Rajavithi Hospital - Chareonwat, Apiwan (Journal of The Department of Medical Services, 2024)
Background: Insomnia is a common problem among the elderly, causing many health problems resulting in the quality of life. In Thailand, it was found that the prevalence and associated factors of insomnia among the elderly differed from the study in each area. Therefore, this study was conducted to study the prevalence and related factors of insomnia patients in outpatient department of family medicine Rajavithi Hospital. Objective: This study examined the prevalence and factors associated with insomnia in elderly over 60 years at the Family Medicine Outpatient Department of Rajavithi Hospital. Method: This was a retrospective cross-sectional study. Data were collected by searching the medical records of 12,793 patients over 60 who visited between July 1, - September 30, 2022. Descriptive statistics, independent t-test, chi-square test, Fisher’s exact test, and multiple logistic regression were performed. Result: The prevalence of insomnia was 51.4% (95%CI 50.6, 52.3), but only 3.7% get diagnosed by physicians. 51.2% of the elderly had been prescribed sedative medications. Top fve medications prescribed were lorazepam, amitriptyline, diazepam, clorazepate, and alprazolam. The factors significantly associated with insomnia were female (adj.OR 1.64 [95%CI 1.52, 1.77] p < .001), age 70-79 years old (adj.OR 1.27 [95%CI 1.17, 1.37] p < .001), age over 80 years old (adj.OR 1.87 [95%CI 1.67, 2.09] p < .001), hypertension (adj.OR 1.17 [95%CI 1.05, 1.31] p = .005), peptic ulcer (adj.OR 2.16 [95%CI 1.91,2.45] p < .001), arthritis (adj.OR 1.22 [95%CI 1.07,1.39] p = .004), gastroesophageal reﬂux (adj.OR 1.82 [95%CI 1.42, 2.33] p < .001), cardiovascular disease (adj.OR 1.85 [95%CI 1.44, 2.37] p < .001), cancer (adj.OR 1.64 [95%CI 1.15, 2.34] p = .007), anxiety (adj.OR 12.93 [95%CI 7.97, 20.99] p < .001), depression (adj.OR 6.78 [95%CI 3.20, 14.33] p < .001). Conclusion: The prevalence of insomnia in elderly patients was 51.4%, but only 3.7% get diagnosed by physicians. 51.2% of the elderly had been prescribed sedative medications. The factors associated with insomnia were female, age 70-79 years old, age over 80 years old, hypertension, peptic ulcer, arthritis, gastroesophageal reﬂux, cardiovascular disease, cancer, anxiety, depression.